The Effects of a Reading-Based Intervention on Emotion Processing in Children Who Have Suffered Early Adversity and War Related Trauma - Michalek, Julia E.; Lisi, Matteo; Awad, Deema; Hadfield, Kristin; Mareschal, Isabelle; Dajani, Rana (Frontiers in Psychology, 2021)
Early adversity and trauma can have profound effects on children’s affective development and mental health outcomes. Interventions that improve mental health and socioemotional development are essential to mitigate these effects. We conducted a pilot study examining whether a reading-based program (We Love Reading) improves emotion recognition and mental health through socialisation in Syrian refugee (n=49) and Jordanian non-refugee children (n=45) aged 7-12 years old (M=8.9, 57% girls) living in Jordan. To measure emotion recognition, children classified the expression in faces morphed between two emotions (happy-sad and fear-anger), while mental health was assessed using survey measures of optimism, depression, anxiety, distress, and insecurity. Prior to the intervention, both groups of children were significantly biased to interpret ambiguous facial expressions as sad, while there was no clear bias on the fear-anger spectrum. Following the intervention, we found changes in Syrian refugee children’s bias in emotion recognition away from sad facial expressions, although this returned to pre-intervention levels 2 months after the end of the program. This shift in the bias away from sad facial expressions was not associated with changes in self-reported mental health symptoms. These results suggest a potential positive role of the reading intervention on affective development, but further research is required to determine the longer-term impacts of the program.